ACE2 Is Expressed in Immune Cells That Infiltrate the Placenta in Infection-Associated Preterm Birth - Phetcharawan Lye; Caroline E. Dunk; Jianhong Zhang; Yanxing Wei; Jittanan Nakpu; Hirotaka Hamada; Guinever E. Imperio; Enrrico Bloise; Stephen G. Matthews; Stephen J. Lye (Cells, 2021)
COVID-19 is associated with increased incidence of preterm birth (PTB). We assessed pathways by which SARS-CoV-2 could access the placenta. Placentae, from PTB with or without chorioamnionitis (ChA), or from term pregnancies (n = 12/13/group) were collected. Peripheral blood was collected from healthy pregnant women (n = 6). Second trimester placental explants (16–20 weeks, n = 5/group) were treated with lipopolysaccharide (LPS, to mimic bacterial infection) and ACE2, CCL2, IL-6/8 and TNFα mRNA was assessed. ChA-placentae exhibited increased ACE2 and CCL2 mRNA expression (p < 0.05). LPS increased cytokine and ACE2 mRNA in placental explants. Placental ACE2 protein localized to syncytiotrophoblast, fetal endothelium, extravillous trophoblast and in immune cells-subsets (M1/M2 macrophage and neutrophils) within the villous stroma. Significantly increased numbers of M1 macrophage and neutrophils were present in the ChA-placenta (p < 0.001). Subsets of peripheral immune cells from pregnant women express the ACE2 mRNA and protein. A greater fraction of granulocytes was positive for ACE2 protein expression compared to lymphocytes or monocytes. These data suggest that in pregnancies complicated by ChA, ACE2 positive immune cells in the maternal circulation have the potential to traffic SARS-CoV-2 virus to the placenta and increase the risk of vertical transmission to the placenta/fetus.